Dapatkah religiusitas memoderasi promosi, karakteristik syariah marketing dan kepercayaan terhadap minat masyarakat menabung di bank syariah? - Zakiyatunnaja, Zakiyatunnaja; Pratama, Abdul Aziz Nugraha (Nur Science Institute, 2022)
This study aims to determine the influence of promotion factors, marketing sharia characteristics, and trust in the intention to save in Islamic banks with religiosity as a moderator. This study uses quantitative methods by processing primary data through questionnaires given to the people of Wonosegoro District, Boyolali Regency, who have become customers of Islamic banks. The analytical method used is the MRA (Moderated Regression Analysis) method. Based on the research tests, the results showed that promotion has a negative and insignificant effect on the intention to save. The characteristics of marketing sharia have a positive and significant effect on the intention to save. Trust has a positive and significant effect on the intention to save. The religiosity variable does not moderate promotion, characteristics of Islamic marketing, and belief in the interest in saving.